Attracting Women to the CS Major. - Tillberg, Heather K.; Cohoon, J. McGrath (Frontiers: A Journal of Women Studies, 2005)
The authors of this article state that the growing gender divide in computer science is one of the more perplexing phenomena on college campuses today, especially considering the rising number of high school girls taking advanced science and math courses. Much of the research on this issue focuses on what deters women from entering the field of computer science. Knowledge of the similarities and differences in what attracts students will allow colleges and universities to develop new, proactive approaches for addressing the gender disparity in their computer science (CS) programs. The authors' data were collected from thirty-one focus groups with a total of 182 undergraduate computer science majors. The focus groups were conducted by the principal investigator, J. McGrath Cohoon, or by trained and supervised graduate students. The focus groups were divided in all but one case into exclusively male or exclusively female groups of students. The average number of participants in a focus group was six, but the group sizes ranged from one, in which case a semi- structured interview was conducted, to eighteen.